Evaluation of the hepatoprotective effect of curcumin alone or in combination with vitamin C in methotrexate-induced hepatotoxicity in mice - Dhekra Hasan Khudair; Ali Ismail. Al-Gareeb (Journal of the Pakistan Medical Association)
Objective: To assess the hepatoprotective effect of curcumin and/or vitamin C in methotrexate-induced hepatotoxicity. Method: The experimental study was conducted at the Department of Pharmacology, College of Medicine, and the Iraqi Centre for Cancer and Medical Genetic Research, Mustansiriya University, Baghdad, Iraq, from Nov 12, 2020, to June 1, 2021, and comprised Swiss albino female mice aged 3-4 months and weighing 30-40g each. The mice were divided into 5 groups and treated for 10 days. Group 1 received distilled water, group 2 received single-dose methotrexate on the 10th day of the trial, group 3 was treated with curcumin plus methotrexate, group 4 was treated with vitamin C plus methotrexate, and group 5 was treated with curcumin and vitamin C plus methotrexate. Parameters measured were serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and lactate dehydrogenase, as well as hepatic tissue malondialdehyde, superoxide dismutase and glutathione. Data was analysed using SPSS 16. Results: There were 35 mice; 7(20%) in each of the 5 groups. Hepatoprotection produced by curcumin as reflected by a decrease in lactate dehydrogenase and malondialdehyde levels was significant (p<0.05). Vitamin C also produced a significant hepatoprotection, demonstrated by a decrease in alanine aminotransferase, alkaline phosphatase, lactate dehydrogenase and malondialdehyde levels. The combination of curcumin and vitamin C reflected an additive effect demonstrated by a significant decrease in malondialdehyde (p<0.05). Conclusion: Curcumin and/or vitamin C provided hepatoprotection against methotrexate-induced hepatotoxicity through modulation of oxidative stress biomarkers. Key Words: Phosphatase, Transaminase, Curcumin, Methotrexate, Oxidative Stress, Ascorbic, Glutathione, Liver, Dismutase, Aminotransferases, Dehydrogenases, Malondialdehyde